PENGARUH LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR - Fredy Fredy; Anna Francis Kakupu; Salman Alparis Sormin (Program Studi PGSD Universitas Flores, 2022)
The purpose of this study was to determine whether there was an influence of the family environment on the learning achievement of grade IV A students at SD Inpres Mangga Dua Merauke. This type of research is quantitative research. Respondents taken were 36 students. Data collection techniques using questionnaires and documentation. The questionnaire was used to obtain data on family environment variables and documentation was used to obtain data on student achievement. The data analysis technique used correlation test, hypothesis test (t test), and determination test. Correlation test to determine the relationship of the family environment to student achievement. Hypothesis test (t test) to determine whether there is an influence of the family environment on student achievement. Determination test to determine the influence of the family environment on student achievement. The results showed that there was a significant influence of the family environment on the learning achievement of grade IV A students at SD Inpres Mangga Dua Merauke. This is evidenced by the results of the t test where the value of t count> t table (5,299> 2,032). The family environment has a strong positive contribution to student achievement with a correlation value of 0.673. The magnitude of the influence of the family environment on student achievement is 45.2%.